Russian Plekhanov University of Economics, Moscow, Russian Federation - Aigul Raissova, Gulbanu Kabzhanova, Rahila Aubakirova,; Dmitrii V. Enygin, Nataliia Yu. Fominykh, (Opción, 2019)
The article is devoted to the discussion of the results of the study of readiness for the use of smart resources in the process of learning a foreign language via comparative qualitative research methods. The results show that although students are aware of the benefits of using modern information and computer technologies in learning English, they have not developed a readiness for the rational and systematic use of smart resources. In conclusion, the changing paradigm of education and the increasing role of foreign language training show that metacompetence is becoming an important component of the graduate’s professional competence.